Integrated Crop Management for eco-friendly crop production - Kumar, Dinesh (Indian Farming, 2015)
After the observation of negative effects of the green revolution on natural resources, a need was felt for developing new systems of management. Although much emphasis is being given on basic research but, there is a growing need to popularize and facilitate research on agronomic aspects of different crops and systems. These will include studies ranging from land preparation through seeding and propagation and management up to har-vesting. It is only under such conditions that the people who produce food for increasing populations, especially in the tropical developing countries, would adopt integrated management systems of agriculture, which to date have had very little emphasis and research backing. The future success of crop production lies in the growth of crops with less environmental stress. Thus, integrated crop management strategies have a great promise in protecting the fragile environment and increasing the farm income.